Bicentennial: the battle of Ayacucho, an emblematic event - Vásquez Gonzales, José María (2021)
Ayacucho's battle of 1824, one is of the emblematic events celebrated by all the Peru. We have been interested in the theme, since it has been very well-thumbed, but in negative form, affirming that there was no battle the December 9, 1824, because it is so Dónde had it soldiers were buried dead do you battle of 1824 of happiness? Those that deny her ask themselves. We affirmed categorically that Ayacucho's battle if it came true and the dead soldiers were buried at the Christian temples so much of Quinua's town like in give them Ayacucho's city. In addition, we confirmed than the day Thursday December 9, 1824, a simulacrum was nothing but that a great battle at Ayacucho's historic Pampa, where the Ejercitó Joined Liberating expired came true. For this fact Ayacucho, it is considered THE AMERICAN FREEDOM'S CRADLE.